2010
DOI: 10.1186/1743-7075-7-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dietary protein on lipid metabolism-related gene expression in porcine adipose tissue

Abstract: BackgroundHigh dietary protein can reduce fat deposition in animal subcutaneous adipose tissue, but little is known about the mechanism.MethodsSixty Wujin pigs of about 15 kg weight were fed either high protein (HP: 18%) or low protein (LP: 14%) diets, and slaughtered at body weights of 30, 60 or 100 kg. Bloods were collected to measure serum parameters. Subcutaneous adipose tissues were sampled for determination of adipocyte size, protein content, lipid metabolism-related gene expression, and enzyme activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 66 publications
(69 reference statements)
4
62
1
Order By: Relevance
“…Berndt et al (2007) reported that increased FAS gene expression in human adipose tissue was significantly related to visceral fat accumulation. Likewise, the down-regulation of ME and G6PD gene expressions has been associated with the reduction in lipogenic activity resulting in decreased fat accumulation (Zhao et al, 2010). The CPT activity did not significantly change in HF and HF-HV groups, but decreased in HF-MV and HF-LV groups relative to that of the NC group.…”
Section: Hepatic Lipid Regulating Enzymes and β-Oxidation Activitiesmentioning
confidence: 97%
“…Berndt et al (2007) reported that increased FAS gene expression in human adipose tissue was significantly related to visceral fat accumulation. Likewise, the down-regulation of ME and G6PD gene expressions has been associated with the reduction in lipogenic activity resulting in decreased fat accumulation (Zhao et al, 2010). The CPT activity did not significantly change in HF and HF-HV groups, but decreased in HF-MV and HF-LV groups relative to that of the NC group.…”
Section: Hepatic Lipid Regulating Enzymes and β-Oxidation Activitiesmentioning
confidence: 97%
“…Studies have demonstrated that SCD facilitates more accessible pool of monounsaturated fatty acids in adipose tissue and therefore, regulate the synthesis of triglyceride (Postic and Girard, 2008). Furthermore, adipocyte-fatty acid binding proteins (A-FABP) and lipoprotein lipase (LPL) have identified as regulators of lipid metabolism in adipose tissue because they are able to modulate the expression of genes involved in lipid metabolism or fatty acids transportation (Zhao et al, 2010). Despite an increase of dietary energy intake (in terms of fat) can improve the digestion and absorption of other nutrients, it may also upregulate the expression of lipogenic genes which eventually cause an increased de novo synthesis of free fatty acid (FFA) resulting higher accumulation of subcutaneous adipose tissue .…”
Section: Fat Depositionmentioning
confidence: 99%
“…FABP4 has been proposed to play a critical role in the balance between lipolysis and lipogenesis in adipocytes (Chmurzynska, 2006). As it appears late during adipogenesis (Spiegelman et al, 1983), FABP4 content has recently been suggested as a valuable marker for lipid content and adipocyte number (Zhao et al, 2010). The gene, acting as a key mediator of intracellular transport and metabolism of fatty acids, is expressed in a differentiation-dependent fashion in adipocytes (Amri et al, 1991;Gregoire et al, 1998).…”
Section: Candidate Genes For Fat Metabolismmentioning
confidence: 99%